MELATONIN DAN MELATONIN RECEPTOR AGONIST SEBAGAI PENANGANAN INSOMNIA PRIMER KRONIS - Ni Luh Putu Ayu Maha Iswari; Anak Ayu Sri Wahyuni (E-Jurnal Medika Udayana, 2013)
Melatonin is a hormone that has an important role in the mechanism of sleep. Hypnotic effects of melatonin and melatonin receptor agonist are mediated via MT1 and MT2 receptors, especially in circadian rhythm pacemaker, suprachiasmatic nucleus, which is worked on the hypothalamic sleep switch. This mechanism is quite different with the GABAergic drugs such as benzodiazepine. Agonist melatonin triggers the initiation of sleep and normalize circadian rhythms so that makes it easier to maintain sleep. The main disadvantage of melatonin in helping sleep maintenance on primary insomnia is that the half life is very short. The solution to this problem is the use of prolonged-release melatonin and melatonin receptor agonist agents such as ramelteon. Melatoninergic agonist does not cause withdrawal effects, dependence, as well as cognitive and psychomotor disorders as often happens on the use of benzodiazepine.